The environment in question : ethics and global issues - Cooper, David Edward; Palmer-Cooper, Joy A. (Routledge, 1992)
Contributors from the UK, USA, Australia and India from a variety of disciplines write on the practical and theoretical issues surrounding the environmental debate. This book is a key introduction to this topical area.